Colombia’s Foreign Policy on integration - Pastrana Buelvas, Eduardo (2016)
During the Administration of President Uribe, the international agenda of Colombia has become securitized and focused on terrorism likewise, it has intensified the bilateral relation with the United States. As a consequence, Latin America and Europe have not received special attention in the Colombian foreign. For these reasons, the author proposes to understand the current orientation of Colombia’s foreign policies on integration could be understood through the lens of what he calls a doctrine of neo Respice Polum (look towards the north).